The Strategies of Academic Library to Serve Net-Generation - Setiawan, Chandra Pratama (Record and Library Journal, 2015)
The  fast  developments  in  information  and  communication  technology  have  rapidly  shaped  and created enormous changes in the way people live and use libraries. The generation who grow in this era is called net generation. Academic libraries, where the majority of the users are the net-generation,  have  started  to  implement  the  concept  of  hybrid  library  as  a  response  of  the technological  advances.  The  trend  of  digital  collections  usage  is  getting  increase,  on  the  other hand,  the  number  of  library  visitor  is  getting  lower  significantly.  The  condition  make  librarians afraid  of  being  abandoned  by  its  users,  whereas  libraries  still  have  many  physical  collections. This paper is written as a result of simple observation in some libraries where the needs of net-generation  has  accommodated.  The  concept  of library  as  place,  and  library  marketing  offer  the solutions to deal with the problem. Libraries can develop and provide some facilities that suitable with  the net-generation  characteristics.  In  addition,  libraries  can  create  some  events  to  promote their services even the collections to attract the users to visit library.